The Mediating Role of Meaninglessness in the Relationship Between Religiosity and Depression - AYTEN, ALİ (ATATURK UNIV, FAC THEOLOGY, 2021)
The research focuses on the relationship and interaction between religiosity, depression, and the sense of meaninglessness. Accordingly, the study aims to determine whether meaninglessness has a mediating role in the effect of religiosity on depression. The research sample consists of 1007 people whose ages range from 18 to 78 (SD=11.33) and who reside in different provinces of Turkey. In order to test the hypotheses developed before the research, a questionnaire form consisting of personal information form, religiosity scale, depression scale, and meaninglessness scale was applied to the participants. The findings of the study revealed that there is a negative relationship among religiosity, depression, and meaninglessness. On the other hand, in the study, positive significant relationships and interactions were found between depression and meaninglessness. Furthermore, mediation analysis showed that meaninglessness is ascertained as a full mediator in the effect of religiosity on depression. The findings obtained as a result of the research were discussed in the light of the literature and some suggestions were made.
Keywords: Psychology of Religion; Religiosity; Depression; Mental Health; Meaninglessness; Meaning in Life; MENTAL-HEALTH; SELF-ESTEEM; LIFE; STRESS; ANXIETY; RELIGIOUSNESS; RISK